The formation of cultural identity through the adaptive digital humanities platform: Evidence of poetry writing among Indonesian children - Sudigdo, Anang; Suroso, Eko; Pamungkas, Onok Yayang; Aji, Daru Tunggul; Inderanata, Rochmad Novian; Jatmiko, Edi; Darheni, Nani; Mukorobin, Nailul (Research Journal in Advanced Humanities, 2026)
This study proposes an intelligent culturally aware mobile learning system that integrates adaptive prompt generation and user interaction analytics to support creative writing processes. Unlike conventional mobile learning applications that primarily focus on content delivery, the proposed system is designed as an adaptive digital architecture consisting of a user interface layer, a cultural knowledge module, an adaptive prompt generation engine, a feedback mechanism, and an interaction analytics component. The system transforms user-generated input, writing progression, and culturally embedded knowledge into structured prompts and iterative feedback cycles, enabling dynamic and personalized learning interactions. To address the limited system-level validation in culturally responsive mobile learning research, this study evaluates the proposed system using both deployment and performance indicators, including usability, feature-level interaction, session duration, daily active use, and implementation fidelity. A quasi-experimental deployment involving 120 users across multiple schools was conducted over eight weeks. The system demonstrated stable real-world operation, high engagement levels, and a System Usability Scale score of 84.2. Interaction analytics indicated consistent feature adoption, particularly within adaptive writing and cultural interaction modules. In addition, outcome analysis revealed significant improvements in user-generated outputs, while structural modeling showed that cultural awareness mediated the relationship between system interaction and performance. These findings position the proposed approach as an intelligent mobile learning system that operationalizes adaptive interaction, cultural knowledge integration, and analytics-based validation within a scalable digital environment.